Terbinafine-induced liver toxicity in the context of a SARS-CoV-2 pandemic: a case report - Bustios Sanchez, Carla (2021)
Terbinafine is a drug that can induce acute liver damage. We present the case of a 40-year-old male patient who developed liver dysfunction after 35 days of terbinafine treatment for onychomycosis. The anatomopathological study showed: acute hepatitis in resolution, in addition to ductopenia and cholestasis. These findings, without a history of viral or autoimmune hepatitis, are consistent with the diagnosis of drug-induced liver damage (DILI). In this report we present the first case in our country of a patient who is affected by an acute liver disease: terbinafine-induced liver injury, to which SARS-CoV-2 infection was later associated in the context of a pandemic.